THE EFFECT OF CREATING TIKTOK VIDEOS ON STUDENTS’ SPEAKING SKILL - Nadhifatuzzahro, Auly; Sulistianingsih, Endang; Sumartono, Sumartono (Universitas Muhammadiyah Semarang, 2025)
This study examined the effect of creating TikTok videos on the speaking skills of the tenth-grade students of SMA Al Irsyad Tegal. The objective of this research was (1) to determine the effect of creating a TikTok video on speaking skills and (2) to describe students’ perception of Creating TikTok on their motivation for speaking skills. This study used a mixed-method approach to answer the research objective. An instrument used in this research was a speaking test. The instruments have been tested for validity and reliability. The study found that there was a difference between the post-test means of the experimental group and the control group. The results of this research showed that creating a TikTok video was successful in improving students’ speaking skills. Based on the questionnaire, students said they had less confidence in speaking English due to a lack of vocabulary. After creating a TikTok video, they said they became more motivated to enrich their vocabulary because the activity is fun, engaging, and not stressful